LITERATUR STUDY OF STUDENTS MATHEMATICAL PROBLEM SOLVING ABILITIES ON HIGHER ORDER THINKING SKILL QUESTIONS FROM VARIOUS LEARNING MODELS - Elia Siska; Muhammad Amin Fauzi (ZERO: Jurnal Sains, Matematika dan Terapan, 2022)
This study aims to determine the results of a literature study on students' mathematical problem solving abilities on higher order thinking skill (HOTS) questions from various learning models. Students' problem solving abilities in identifying elements that are known or needed in solving mathematical problems, formulating mathematical problems, selecting problem solving, and re-examining problem solving to then make solutions in other ways or develop student problem solving when students are faced with math problem. High Order Thinking Skills (HOTS) is a thinking process of students at a higher cognitive level that is developed from various cognitive concepts and methods and learning taxonomies such as problem solving methods, bloom taxonomies, and learning, teaching, and assessment taxonomies. Based on the results of the analysis of the results of the study, it was concluded that students' mathematical problem solving abilities could be improved by applying problem based learning and discovery learning models. And the learning model that is better used is the Problem Based Learning.